Kiwifruit seed oil prevents obesity by regulating inflammation, thermogenesis, and gut microbiota in high-fat diet-induced obese C57BL/6 mice. (March 2019) - Qu, Linlin; Liu, Qingqing; Zhang, Qi; Tuo, Xingxia; Fan, Daidi; Deng, Jianjun; Yang, Haixia
Abstract: Obesity is considered as a chronic disease which seriously affecting people's health and daily life. Kiwifruit ( Actinidia chinensis Planch) seed oil (KSO), as a by-product of kiwifruit processing, is rich in fatty acids. Conventional wisdom holds that KSO has many health benefits, but there is no scientific basis. Here, the relieving effects of KSO on obesity and its potential mechanism were investigated in high-fat diet (HFD)-induced C57BL/6 mice. Mice were divided into four groups: ND (normal diet); HFD; L-KSO and H-KSO (HFD supplemented with 1.0 and 3.0 mL/kg·bw of KSO per day, respectively). Results showed that continuous supplementation KSO for 12 weeks significantly decreased bodyweight, inguinal fat tissue weight, blood glucose, and HOMA-IR index and ameliorated serum lipids accumulation (TC, TG, HDL-C, and LDL-C). Relative mRNA expression of inflammatory cytokines (TNF-α, IL-6, IL-1β, COX-2, and iNOS) was down-regulated and expression of thermogenesis-related genes (PPAR-γ, UCP1, PGC1-α, and PRDM16) was up-regulated in the inguinal fat tissue of KSO treated mice. Principal component analysis showed that the microbial community compositions of four groups were different. KSO supplementation dramatically decreased the Firmicutes -to- Bacteroidetes ratio. Together, our findings demonstrated that long-term supplementation KSO ameliorates obesity by reducing inflammation, adipose thermogenesis and gut microbiota dysbiosis. Graphical abstract: Image 1 Highlights: Long-term dietary of kiwifruit seed oil (KSO) can decrease bodyweight gain of HFD-induced obese mice. KSO supplementation can reduce inflammation and adipose thermogenesis in HFD-induced obese mice. KSO supplementation can ameliorate gut microbiota dysbiosis in HFD-induced obese mice.